Characterization of Moringa oleifera LAM. germplasm collections in the Philippines By DNA fingerprinting - Panes, Vivian A.; Tandoc, Elaine Anne L.; Fortuno, Erica E.; Romero, Gabriel O. (2011)
Moringa oleifera Lam. Or Malunggay is increasing in commercial relevance because of its nutritional, therapeutic and prophylactic properties. However, in the Philippines, there are few studies of Malunggay on the genetic level despite the extensive genetic resources. To contribute to the knowledge about Malunggay, in this study, genetic variation of M. oleifera germplasm collections in the Philippines was analyzed using intersimple sequence repeats (ISSRs) and SRILS as genetic markers. Seventy five accessions of Malunggay cuttings and seeds were collected from different locations in the Philippines. From these cuttings and seeds, genomic DNA was extracted using DNAzol and Zymo plant DNA extraction kits. Twelve ISSRs and nine SRILS primers were used as markers. Genomic DNA was subjected to PCR analysis. The PCR products were run on agarose gels. Then the results were analyzed by scoring the presence (1) and absence (0) of the different bands for all the samples. Polymorphic bands were determined as the bands that were present and absent across the samples. Results showed that there are 8 polymorphic bands using the ISSR primers and 15 of polymorphic bands emerged using the SRILS primers. These results indicate that M. oleifera in the Philippines is genetically diverse. A preliminary analysis was done by using the PAUP software and phylogenetic tree construction is underway. More accessions are currently being optimized for PCR analysis. Hence, the extent of genetic diversity of the Malunggay germplasm collection in the Philippines is yet to be determined statistically.
Keywords: Moringa oleifera; Malunggay (Plant); DNA fingerprinting